Managing diversity, innovation, and infrastructure in digital business - Ray, Nilanjan, 1984- (Business Science Reference, 2019)
"This book presents a variety of practical applications, tools, skills, practices, models, approaches, and strategies that are proving themselves in practice-demonstrating effectiveness with managing diversity and innovation. It also shares a different pattern of research work that will provide a platform for new avenues in overall infrastructure, socioeconomic conditions, and modern tourism business infrastructure"--